Mixing interstitial alloy and preparation method and application thereof

By introducing a silicon sol into the first component of the miscible gap alloy and forming a protective layer, the problem of complex and time-consuming preparation process in the prior art is solved, and the thermal conductivity and service life are improved.

CN119753406APending Publication Date: 2025-04-04BEIJING QIYUE ENVIRONMENTAL PROTECTION TECH CO LTD

Patent Information

Application Number
CN202411967114.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the preparation process of miscible gap alloys is complex and time-consuming, resulting in poor thermal conductivity and short service life.

Method used

The preparation method of miscible gap alloy is optimized by introducing a silicon sol with excellent structural properties and non-absorbing of moisture into the first component and forming a thinner third component protective layer on the basis of the first component and the second component.

Benefits of technology

It reduces the complexity and time-consuming preparation process of miscible gap alloys, improves thermal conductivity and service life, and avoids the degradation of structural performance caused by moisture absorption of sodium silicate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753406A_ABST
    Figure CN119753406A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of heat energy storage, and particularly relates to a miscible interstitial alloy and a preparation method and application thereof. The preparation method comprises the following steps: taking graphite and sodium silicate as a mixed matrix, introducing silica sol, and mixing to form a first component; metal powder is used as a second component; the first component serves as a framework, the second component serves as a carrier, mixing and pressing are conducted, and a first alloy blank is obtained; mixing silica sol, graphite powder and water to form slurry, namely a third component; a third component serves as a protective layer and is sprayed to the surface of the first alloy blank, and a second alloy blank is manufactured; and the second alloy blank is pressed and sintered at the room temperature, and the miscible interstitial alloy is obtained. The heat conductivity coefficient of the prepared miscible interstitial alloy is 61.7 W / mK to 69.3 W / mK, and the miscible interstitial alloy has excellent heat-conducting property and compressive strength; compared with the prior art, the production cycle of the blank in the miscible interstitial alloy is shortened by 86%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal energy storage, and in particular relates to a miscible interstitial alloy and a preparation method and application thereof. Background Art

[0002] Miscible interstitial alloys are a low-cost, low-pollution, high-heat storage energy storage material developed by the University of Newcastle, Australia. This material can store large amounts of renewable energy as heat for a long time, especially in the fields of peak energy storage and thermal energy transfer.

[0003] The international patent with the authorization number WO 2014 / 063191 A1 discloses the definition of miscible interstitial alloy, which is a new type of heat storage material, including: a first component and a second component, the first component is a dense continuous heat-conducting matrix, and the second component is a component in which particles are dispersed throughout the matrix of the first component. The first component and the second component are completely or partially immiscible, and the melting temperature of the first component is much higher than that of the second component. The miscible interstitial alloy is contacted with a heat source to provide a material containing a large amount of heat. The international patent gives a broad definition of miscible interstitial alloys, but does not clearly explain their production process.

[0004] In the prior art, engineering development and heat storage field tests have been carried out on miscible interstitial alloys. The currently disclosed production process of miscible interstitial alloys is: mixing the first component and the second component to obtain a blank; pressing the blank at room temperature and sintering at high temperature to obtain a miscible interstitial alloy. Among them, the first component is composed of graphite powder and a binder, and the binder is generally a saturated sodium silicate aqueous solution or a saturated sodium aluminate solution. The initial state of the first component is a solid-liquid mixed clay state, so the first component needs to be dried and a series of subsequent complex treatment processes during the processing, and finally prepared into a powder with a particle size of ≤40μm. However, in the prior art, drying alone requires 24h to 36h, which makes the processing process of the blank time-consuming, resulting in a complex and time-consuming preparation process of the miscible interstitial alloy. Summary of the invention

[0005] In order to solve the problem that the preparation process of the miscible interstitial alloy is complicated and time-consuming during the preparation of the miscible interstitial alloy, the present invention provides a miscible interstitial alloy and a preparation method and application thereof.

[0006] The miscible interstitial alloy of the present invention is a first component as a skeleton, a second component as a carrier and a third component as a protective layer. The first component and the second component are mixed and then pressed to obtain a first alloy blank; the third component is sprayed on the surface of the first alloy blank to form a protective layer to obtain a second alloy blank; the second alloy blank is pressed and sintered at room temperature to obtain a miscible interstitial alloy. Among them, the first component is a mixed matrix of graphite and sodium silicate, and silica sol is introduced to mix and form. By introducing silica sol with better structural performance and non-hygroscopicity into the first component, and the mixing method of the first component is to directly mix graphite powder, sodium silicate powder and silica sol; on the one hand, the influence of sodium silicate with poor thermal conductivity on the thermal conductivity of the first component is reduced, and on the other hand, the non-hygroscopicity of silica sol is used to reduce the influence of sodium silicate's easy moisture absorption in the air, and avoid the influence on the structural performance of the miscible interstitial alloy skeleton. More importantly, by optimizing the mixing method of the first component, the problem of complex and time-consuming blank preparation process is further solved.

[0007] In addition, in the prior art, the mass fraction of sodium silicate in the first component is 38.5wt%, and the large amount of sodium silicate added reduces the thermal conductivity of the miscible interstitial alloy. Sodium silicate absorbs moisture in the air very seriously, and its structural performance decreases rapidly after absorbing moisture, which increases the storage cost of the miscible interstitial alloy and reduces its service life; more importantly, during the high-temperature sintering process, since the sintering temperature is 50℃ to 80℃ higher than the melting point of the second component, the second component on the surface of the miscible interstitial alloy sweats and flows seriously, which causes the miscible interstitial alloy to crack and absorb moisture, reducing its service life.

[0008] The present invention introduces silica sol with better structural performance and no hygroscopicity into the first component, and utilizes the non-hygroscopicity of silica sol to weaken the influence of sodium silicate's easy moisture absorption in the air, thereby avoiding the influence on the skeleton structural performance of the miscible interstitial alloy. At the same time, on the basis of the first component and the second component, a thinner third component layer is introduced on the surface of the miscible interstitial alloy, and the third component is composed of graphite powder, silica sol and water. The sintered product of silica sol has the advantages of high structural strength and no hygroscopicity, so that the single-component layer has the advantages of preventing the second component from sweating, high density, structural strength and no surface cracking; and after the third component is introduced, it will not affect the original excellent thermal conductivity and energy storage capacity of the miscible interstitial alloy. The first purpose of the present invention is to provide a method for preparing a miscible interstitial alloy, comprising the following steps:

[0009] S1. Graphite and sodium silicate are used as a mixed matrix, and silica sol is introduced to form a first component.

[0010] Metal powder is used as the second component.

[0011] The first component is used as a skeleton and the second component is used as a carrier, and they are mixed to obtain a blank.

[0012] It should be noted that the first component, as a dense and continuous thermal conductive matrix of the miscible interstitial alloy and also the skeleton of the miscible interstitial alloy, needs to have the characteristics of good thermal conductivity and high structural strength. The first component in the prior art is composed of graphite powder and a binder, and sodium silicate is used as a binder. The thermal conductivity of sodium silicate is small, about 1W / (m·K). The small thermal conductivity leads to poor thermal conductivity of the synthesized miscible interstitial alloy, thereby affecting the energy storage effect of the miscible interstitial alloy; in addition, the moisture absorption phenomenon of sodium silicate in the air is very serious. After moisture absorption, the structural properties of the miscible interstitial alloy decrease rapidly, resulting in poor mechanical properties, thereby reducing its service life. Therefore, the characteristic of the present invention lies in that, by introducing silica sol which absorbs moisture very weakly after sintering into the first component, on the one hand, the content of sodium silicate in the first component is reduced by the addition of silica sol, thereby reducing the influence of sodium silicate with poor thermal conductivity on the thermal conductivity of the first component, thereby affecting the thermal conductivity of the miscible interstitial alloy; on the other hand, by utilizing the extremely weak moisture absorption property of silica sol after sintering, the influence of sodium silicate's easy moisture absorption in the air is weakened, thereby avoiding the influence on the skeleton structure performance of the miscible interstitial alloy, thereby reducing the storage cost of the miscible interstitial alloy and improving the service life of the miscible interstitial alloy.

[0013] In addition, by optimizing the mixing method of the first component, graphite powder, sodium silicate powder and silica sol are directly mixed to obtain the first component. The mixing method of the first component of the present invention avoids the prior art of mixing graphite powder with a saturated sodium silicate aqueous solution to obtain mixed clay, and subsequently requires a series of complex processing processes such as drying, thereby solving the problem of complex and time-consuming blank preparation process.

[0014] The present invention controls the mass fraction of sodium silicate and silica sol in the first component to be much lower than the mass fraction of sodium silicate in the saturated aqueous solution of sodium silicate in the prior art, which is 38.5wt%, so as to avoid the influence of a large amount of sodium silicate added on the thermal conductivity of the miscible interstitial alloy, thereby causing the structural performance of the miscible interstitial alloy to decrease. Therefore, the mass fraction of sodium silicate in the first component of the present invention is preferably 2wt% to 6wt%, and the mass fraction of silica sol in the first component is preferably 0.5wt% to 2.5wt%. In addition, in order to make the first component mixed evenly, the preferred mixing method of the present invention is mechanical stirring, and the stirring time is 15min to 30min.

[0015] It should be noted that the second component is used as the main carrier of phase change energy storage, and the second component is dispersed as particles in the entire continuous thermal conductive matrix of the first component, and the second component has the characteristics of large melting latent heat, high energy storage, large thermal conductivity and no supercooling. The preferred second component of the present invention is a metal powder, and the metal powder is one of Al, Cu, Zn, Sn and Al-Si alloy powder, and the particle size of the metal powder is 100μm to 500μm.

[0016] Preferably, the mass fraction of graphite powder in the first component is 48wt% to 51wt%.

[0017] Preferably, the mass fraction of the first component in the blank is 50wt%.

[0018] S2. Pressing the blank at room temperature to form a first alloy blank.

[0019] The uniformly mixed billet powder is placed in a first mold and pressed at room temperature to form a first alloy billet. Preferably, in the present invention, the pressing pressure is 5 MPa to 8 MPa, and the holding time is 5 min to 10 min.

[0020] S3, mixing silica sol, graphite powder and water to form a slurry, i.e. the third component.

[0021] The third component is used as a protective layer and sprayed on the surface of the first alloy billet to form a second alloy billet.

[0022] It should be noted that the present invention introduces a single-component layer formed by a thinner third component on the surface of the first alloy billet to form a second alloy billet. Since the sintering temperature is higher than the melting point of the second component, if the first alloy billet, which is pressed by mixing the first component and the second component, is directly sintered at high temperature without uniformly wrapping the third component on the outer layer of the first alloy billet as a protective layer; during the sintering process, the component two on the surface of the miscible interstitial alloy made of the first component and the second component will heat up and expand, melt and crack the thin layer of the first component on the surface and form flow marks on the surface; after one sintering, the miscible interstitial alloy loses 4% to 8% of its weight ratio, and the melted second component will form a hollow channel near the surface of the miscible interstitial alloy, which will cause the second component near the surface to continue to sweat and flow out during subsequent sintering and service, reducing the thermal conductivity and energy storage capacity of the miscible interstitial alloy.

[0023] The preferred third component of the present invention is a slurry formed by mixing silica sol, graphite and solvent, and the mass fraction of silica sol in the preferred third component is 15wt% to 20wt%. Since the sintered product of silica sol has the advantages of high structural strength and non-hygroscopicity, and the single-component layer formed by the third component is used as a protective layer of the first alloy billet, the phenomenon of cracking and overall expansion of the surface of the miscible interstitial alloy due to the melting of the second component during the high-temperature sintering process of the miscible interstitial alloy is avoided. In addition, the viscosity of the third component is preferably controlled to be 30mPa·s to 38m·Pas. The spraying thickness of the preferred third component of the present invention is 0.7mm to 1mm, ensuring that a dense layer of a certain thickness is formed on the surface of the first alloy billet to hinder the melting of the second component.

[0024] S4. Pressing the second alloy billet at room temperature to form a final billet, and sintering the final billet to obtain a miscible interstitial alloy.

[0025] The second alloy billet is placed in the second mold and continued to be pressed at room temperature to form a final billet. The preferred pressing pressure of the present invention is 8MPa to 12MPa, and the holding time is 5min to 10min. By setting the pressure of the second alloy billet higher than that of the first alloy billet, the final billet is prevented from cracking and collapsing during placement, drying and sintering at room temperature. The diameter, length and width of the second mold are 1.5mm to 2mm larger than those of the first mold.

[0026] It should be noted that the present invention puts the final blank into a drying furnace for drying before high-temperature sintering. The drying temperature adopted by the present invention is 120℃~160℃, and the drying time is 300min~600min; the corresponding drying time is determined according to the size of the final blank, thereby promoting the complete volatilization of the free moisture in the final blank, and ensuring that there is no sudden increase in vapor pressure during the sintering process to cause the final blank to crack. The specific sintering process of the present invention is as follows: the dried final blank is placed in a sintering furnace, and sintered by setting a staged sintering process. The dried final blank is first heated to an intermediate temperature at a heating rate of 3℃ / min~5℃ / min and kept warm for 40min~60min, then heated to a target temperature at a heating rate of 1℃ / min~2℃ / min and kept warm, and finally cooled to room temperature at a cooling rate of 5℃ / min~10℃ / min.

[0027] It should also be noted that during the sintering process, the intermediate temperature of sintering is [0.5T m -(0~50)]℃; the target sintering temperature is [T m +(50~80)]℃, where T mis the melting point of the second component. Since graphite will oxidize and lose in air above 450°C, the sintering atmosphere is determined as follows: if the second component is a low melting point metal, such as Zn and Sn, it can be sintered directly in air; if the second component is a medium to high melting point metal, with a melting point ≥500°C, then sintering should be carried out in a vacuum, nitrogen or inert gas atmosphere. The holding time at the target temperature varies with the shape and size of the block, and the calculation formula is shown in formula (1):

[0028] t = εH / 10 Formula (1);

[0029] In formula (1), t is the holding time of sintering at the target temperature, in h; H is the final billet thickness, in mm; ε is the final billet width B, in mm; ε is the correction factor for time t, if B ≥ 2H, then ε takes a value of 1.1 to 1.3. The larger the block, the longer the holding time. In addition, no mechanical pressure is applied during the sintering process.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] In the process of preparing miscible interstitial alloys, the present invention uses graphite and sodium silicate as a mixed matrix, introduces silica sol, and mixes to form a first component; and uses metal powder as the second component; the first component is used as a skeleton, and the second component is used as a carrier, and mixed to obtain a blank. The present invention optimizes the mixing method of the first component: directly mixing graphite, sodium silicate and silica sol, thereby avoiding the first component in the prior art being a solid-liquid mixed clay state, thereby requiring a series of complex processes such as drying to prepare the first component. The problem of the complicated and time-consuming preparation process of miscible interstitial alloys is solved, and miscible interstitial alloys can be prepared by the present invention.

[0032] In the process of preparing the miscible interstitial alloy, the present invention uses graphite and sodium silicate as a mixed matrix, and introduces silica sol to form a first component. On the basis of the mixed matrix, the present invention introduces silica sol with better structural performance and extremely weak moisture absorption after sintering as the raw material of the first component. On the one hand, the content of sodium silicate in the first component is reduced by adding silica sol, thereby controlling the mass fraction of sodium silicate and silica sol in the first component, avoiding the influence of a large amount of sodium silicate on the thermal conductivity of the miscible interstitial alloy; on the other hand, the extremely weak moisture absorption property of silica sol after sintering is utilized to weaken the influence of sodium silicate's easy moisture absorption in the air, avoiding the influence on the skeleton structure performance of the miscible interstitial alloy, thereby reducing the storage cost of the miscible interstitial alloy and improving the service life of the miscible interstitial alloy.

[0033] In the process of preparing the miscible interstitial alloy, silica sol, graphite powder and water are mixed on the basis of the first alloy blank made of the first component and the second component to form a slurry, i.e., the third component. By introducing the third component, a thin layer of the third component is evenly wrapped on the outer surface of the first alloy blank as a protective layer. The sintered product of the silica sol in the third component has the advantages of high structural strength and extremely weak moisture absorption after sintering. Since the sintering temperature is higher than the melting point T of the second component, the sintering temperature is 100°. m , which prevents the second component on the surface of the final billet from heating up and expanding during the sintering process, melting and cracking the thin layer of the first component on the surface and forming flow marks on the surface. After one sintering, the miscible interstitial alloy loses 4% to 8% of its weight, and the melted second component forms a hollow channel near the surface of the miscible interstitial alloy, which causes the second component near the surface to continue to sweat out during subsequent sintering and service, further reducing the thermal conductivity and energy storage capacity of the alloy. At the same time, the introduction of the third component will not affect the original excellent thermal conductivity and energy storage capacity of the miscible interstitial alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a diagram of the miscible interstitial alloy made in Example 1 of the present invention.

[0035] Figure 2 This is a diagram of the miscible interstitial alloy made in comparative example 7 of the present invention; wherein (a) is an appearance diagram of moisture absorption cracking after drying, (b) is a cross-sectional morphology diagram, (c) is an appearance diagram of the second component being melted out after sintering, and (d) is an appearance diagram of the second component being melted out after sintering. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings.

[0037] It should be noted that the sources of the materials of the present invention are as follows:

[0038] The graphite powder of the present invention is purchased from Shenzhen Jinda Power Technology Co., Ltd., and has a particle size of 40 μm to 60 μm.

[0039] The sodium silicate powder of the present invention is purchased from Gongyi Borun Refractory Material Co., Ltd., with a particle size of 40 μm to 80 μm and a modulus of 3.0 to 3.4.

[0040] The silica sol of the present invention was purchased from Shandong Guohua Co., Ltd. The silica sol is a slightly milky white solution with a density of 1.28 g / cm 3 ~1.3g / cm 3 , viscosity ≤28mPas (20℃).

[0041] The metal powder of the present invention is purchased from Qinghe County Aoshuo Metal Materials Co., Ltd., and the particle size of the metal powder is 100 μm to 500 μm.

[0042] Example 1

[0043] This embodiment provides a method for preparing a miscible interstitial alloy.

[0044] S1. Graphite and sodium silicate are used as a mixed matrix, and silica sol is introduced to form a first component.

[0045] Metal powder is used as the second component.

[0046] The first component is used as a skeleton and the second component is used as a carrier, and they are mixed to obtain a blank.

[0047] 1.1) 6% sodium silicate, 1.5% silica sol, 42.5% water and 50% graphite powder are placed in a sealed container, wherein the volume of the mixed slurry is less than 35% of the volume of the sealed container, and the sealed container is placed in a three-dimensional oscillating mixer at a rotation speed of 20 r / min and a mixing time of 30 min to obtain a first component.

[0048] 1.2) 500 g of the first component and 500 g of Al metal powder were fully mixed in a three-dimensional oscillating mixer for 300 min at a rotation speed of 20 r / min to obtain a blank.

[0049] S2. Place the blank into a first mold and perform pressing at room temperature with a pressing pressure of 8 MPa and a holding time of 10 min to produce a first alloy blank.

[0050] S3, mixing silica sol, graphite powder and water to form a slurry, i.e. the third component.

[0051] The third component is used as a protective layer and sprayed on the surface of the first alloy billet to form a second alloy billet.

[0052] 3.1) Saturated silica sol and water are mixed, stirred thoroughly and then prepared to obtain an 18 wt % silica sol aqueous solution.

[0053] 3.2) 500 g of silica sol aqueous solution and 500 g of graphite powder were mixed evenly, and then sufficient water was added to form a slurry, and the viscosity of the slurry was controlled to be 35.0 mPas to obtain the third component.

[0054] 3.3) The third component is uniformly sprayed onto the surface of the first alloy billet using a spraying machine with a spraying thickness of 0.78 mm to produce a second alloy billet.

[0055] S4. Pressing the second alloy billet at room temperature to form a final billet, and sintering the final billet to obtain a miscible interstitial alloy.

[0056] 4.1) The second alloy billet is placed in a second mold and continued to be pressed at room temperature at a pressing pressure of 12 MPa and a holding time of 10 min to form a final billet, wherein the diameter / length / width and height of the second mold are all 1.2 mm larger than the first mold.

[0057] 4.2) The final billet is placed in a drying furnace for drying at a temperature of 120°C for 300 min. The dried final billet is then heated to 400°C at a heating rate of 3°C / min and kept at that temperature for 40 min. The temperature is then increased at a heating rate of 1°C / min to a target temperature of 700°C. After the temperature is kept at that temperature for 2 h, the temperature is cooled to room temperature at a cooling rate of 5°C / min to obtain a miscible interstitial alloy.

[0058] Example 2

[0059] This embodiment provides a method for preparing a miscible interstitial alloy.

[0060] S1. Graphite and sodium silicate are used as a mixed matrix, and silica sol is introduced to form a first component.

[0061] Metal powder is used as the second component.

[0062] The first component is used as a skeleton and the second component is used as a carrier, and they are mixed to obtain a blank.

[0063] 1.1) 4% sodium silicate, 1% silica sol, 44% water and 51% graphite powder are placed in a sealed container, wherein the volume of the mixed slurry is less than 35% of the volume of the sealed container, and the sealed container is placed in a three-dimensional oscillating mixer at a rotation speed of 20 r / min and a mixing time of 30 min to obtain a first component.

[0064] 1.2) 500 g of the first component and 500 g of Al metal powder were fully mixed in a three-dimensional oscillating mixer for 300 min at a rotation speed of 20 r / min to obtain a blank.

[0065] S2. Place the blank into a first mold and perform pressing at room temperature with a pressing pressure of 5 MPa and a holding time of 5 min to produce a first alloy blank.

[0066] S3, mixing silica sol, graphite powder and water to form a slurry, i.e. the third component.

[0067] The third component is used as a protective layer and sprayed on the surface of the first alloy billet to form a second alloy billet.

[0068] 3.1) Saturated silica sol and water are mixed to obtain a 15 wt % silica sol aqueous solution.

[0069] 3.2) 500 g of silica sol aqueous solution and 500 g of graphite powder were mixed evenly, and then sufficient water was added to form a slurry, and the viscosity of the slurry was controlled to be 35.0 mPas to obtain the third component.

[0070] 3.3) The third component is uniformly sprayed onto the surface of the first alloy billet using a spraying machine with a spraying thickness of 0.78 mm to produce a second alloy billet.

[0071] S4. Pressing the second alloy billet at room temperature to form a final billet, and sintering the final billet to obtain a miscible interstitial alloy.

[0072] 4.1) The second alloy billet is placed in a second mold and continued to be pressed at room temperature at a pressing pressure of 8 MPa and a holding time of 5 min to produce a final billet, wherein the diameter / length / width and height of the second mold are all 1.2 mm larger than the first mold.

[0073] 4.2) The final billet is placed in a drying furnace for drying at a temperature of 120°C for 300 min. The dried final billet is then heated to 400°C at a heating rate of 5°C / min and kept at that temperature for 60 min. The temperature is then increased at a heating rate of 2°C / min to a target temperature of 700°C. After the temperature is kept at that temperature for 2 h, the temperature is cooled to room temperature at a cooling rate of 5°C / min to obtain a miscible interstitial alloy.

[0074] The difference between this embodiment and embodiment 1 is:

[0075] In the first component of this embodiment, sodium silicate accounts for 4% of the total mass of the first component, and silica sol accounts for 1% of the total mass of the first component.

[0076] Example 3

[0077] This embodiment provides a method for preparing a miscible interstitial alloy.

[0078] S1. Graphite and sodium silicate are used as a mixed matrix, and silica sol is introduced to form a first component.

[0079] Metal powder is used as the second component.

[0080] The first component is used as a skeleton and the second component is used as a carrier, and they are mixed to obtain a blank.

[0081] 1.1) 2% sodium silicate, 0.5% silica sol, 49.5% water and 48% graphite powder are placed in a sealed container, wherein the volume of the mixed slurry is less than 35% of the volume of the sealed container, and the sealed container is placed in a three-dimensional oscillating mixer at a rotation speed of 20 r / min and a mixing time of 30 min to obtain a first component.

[0082] 1.2) 500 g of the first component and 500 g of Al metal powder were fully mixed in a three-dimensional oscillating mixer for 300 min at a rotation speed of 20 r / min to obtain a blank.

[0083] S2. Place the blank into a first mold and perform pressing at room temperature with a pressing pressure of 7 MPa and a holding time of 8 min to produce a first alloy blank.

[0084] S3, mixing silica sol, graphite powder and water to form a slurry, i.e. the third component.

[0085] The third component is used as a protective layer and sprayed on the surface of the first alloy billet to form a second alloy billet.

[0086] 3.1) Saturated silica sol and water are mixed to obtain a 20 wt % silica sol aqueous solution.

[0087] 3.2) 500 g of silica sol aqueous solution and 500 g of graphite powder were mixed evenly, and then sufficient water was added to form a slurry, and the viscosity of the slurry was controlled to be 35.0 mPas to obtain the third component.

[0088] 3.3) The third component is uniformly sprayed onto the surface of the first alloy billet using a spraying machine with a spraying thickness of 0.78 mm to produce a second alloy billet.

[0089] S4. Pressing the second alloy billet at room temperature to form a final billet, and sintering the final billet to obtain a miscible interstitial alloy.

[0090] 4.1) The second alloy billet is placed in a second mold and continued to be pressed at room temperature with a pressing pressure of 8 MPa and a holding time of 10 min to produce a final billet, wherein the diameter / length / width and height of the second mold are all 1 mm larger than the first mold.

[0091] 4.2) The final billet is placed in a drying furnace for drying at a temperature of 120°C for 300 min. The dried final billet is then heated to 400°C at a heating rate of 4°C / min and kept at that temperature for 50 min. The temperature is then increased at a heating rate of 1°C / min to a target temperature of 700°C. After the temperature is kept at that temperature for 2 h, the temperature is cooled to room temperature at a cooling rate of 5°C / min to obtain a miscible interstitial alloy.

[0092] The difference between this embodiment and embodiment 1 is:

[0093] In the first component of this embodiment, sodium silicate accounts for 2% of the total mass of the first component, and silica sol accounts for 0.5% of the total mass of the first component.

[0094] Comparative Example 1

[0095] This comparative example provides a method for preparing a miscible interstitial alloy.

[0096] 1.1) 1% sodium silicate, 49% water and 50% graphite powder are placed in a sealed container, wherein the volume of the mixed slurry is less than 35% of the volume of the sealed container, and the sealed container is placed in a three-dimensional oscillating mixer at a rotation speed of 20 r / min and a mixing time of 30 min to obtain a first component.

[0097] 1.2) 500 g of the first component and 500 g of Al metal powder were fully mixed in a three-dimensional oscillating mixer for 300 min at a rotation speed of 20 r / min to obtain a blank.

[0098] 1.3) The blank is placed in a first mold and pressed at room temperature with a pressing pressure of 8 MPa and a holding time of 10 min to produce a first alloy blank.

[0099] 1.4) placing the first alloy billet into a drying furnace for drying at a temperature of 120°C for 300 min, heating the dried first alloy billet to 400°C at a heating rate of 3°C / min and keeping the temperature for 40 min, then heating the billet to a target temperature of 700°C at a heating rate of 1°C / min, keeping the temperature for 2 h, and cooling the billet to room temperature at a cooling rate of 5°C / min to obtain a miscible interstitial alloy.

[0100] The difference between this comparative example and Example 1 is:

[0101] In this comparative example, no third component was added.

[0102] Comparative Example 2

[0103] This comparative example provides a method for preparing a miscible interstitial alloy.

[0104] The difference between this comparative example and Example 1 is:

[0105] In this comparative example, no silica sol is added to the first component and the mass fraction of sodium silicate in the first component is 2.5%.

[0106] Comparative Example 3

[0107] This comparative example provides a method for preparing a miscible interstitial alloy.

[0108] The difference between this comparative example and Example 1 is:

[0109] In this comparative example, no silica sol is added to the first component and the mass fraction of sodium silicate in the first component is 5%.

[0110] Comparative Example 4

[0111] This comparative example provides a method for preparing a miscible interstitial alloy.

[0112] The difference between this comparative example and Example 1 is:

[0113] In this comparative example, no silica sol is added to the first component and the mass fraction of sodium silicate in the first component is 7.5%.

[0114] Comparative Example 5

[0115] This comparative example provides a method for preparing a miscible interstitial alloy.

[0116] The difference between this comparative example and Example 1 is:

[0117] In this comparative example, no silica sol is added to the first component and the mass fraction of sodium silicate in the first component is 10%.

[0118] Comparative Example 6

[0119] This comparative example provides a method for preparing a miscible interstitial alloy.

[0120] The difference between this comparative example and Example 1 is:

[0121] In this comparative example, no silica sol is added to the first component and the sodium silicate in the first component is saturated sodium silicate.

[0122] Comparative Example 7

[0123] This comparative example provides a method for preparing a miscible interstitial alloy.

[0124] This comparative example is prepared according to the experimental method of the prior art https: / / doi.org / 10.1016 / j.solener.2018.11.048, and the specific preparation process is as follows:

[0125] 1.1) Sodium silicate is dissolved in water to prepare a saturated sodium silicate solution with a mass fraction of 38.5%. 500 g of the saturated sodium silicate solution and 500 g of graphite powder are selected and placed in a slurry mixer and stirred for 30 minutes to obtain a first component slurry.

[0126] 1.2) Manually divide the first component slurry into multiple slurry blocks of 10-20 mm × 10-20 mm, place them on a stainless steel mesh, air-dry for 2 hours, and then put them into a high-temperature drying oven, set the drying temperature to 250°C, and the drying time to 2160 minutes to obtain concrete slurry blocks.

[0127] 1.3) Put the concrete slurry block into a grinding mill, take it out after grinding for 10 minutes, and use a powder sieve to sieve out 40μm-60μm graphite / sodium silicate concrete powder, which is the first component.

[0128] 1.4) Weigh 500 g of the first component, 50 g of water and 500 g of the second component, put them into a three-dimensional oscillating mixer and mix them thoroughly for 30 minutes at a rotation speed of 20 r / min to obtain a blank.

[0129] 1.5) The blank is placed in the first mold and pressed at room temperature with a pressing pressure of 8 MPa and a holding time of 10 min to produce a final blank.

[0130] 1.6) The final billet is placed in a drying furnace for drying at a temperature of 120°C for 300 min. The dried final billet is then heated to 400°C at a heating rate of 3°C / min and kept at that temperature for 40 min. The temperature is then increased at a heating rate of 1°C / min to a target temperature of 700°C. After the temperature is kept at that temperature for 2 h, the temperature is cooled to room temperature at a cooling rate of 5°C / min to obtain a miscible interstitial alloy.

[0131] Experimental testing

[0132] 1. Appearance analysis

[0133] The present invention performs appearance analysis on the miscible interstitial alloys prepared in Examples 1 to 3 and Comparative Examples 1 to 6 after 30 days of storage. The results are shown in Table 1. The present invention performs appearance analysis on the miscible interstitial alloys prepared in Example 1 after 180 days of storage. The results are shown in Table 1. Figure 1 shown.

[0134] Table 1 Appearance of miscible interstitial alloys prepared in Examples 1 to 3 and Comparative Examples 1 to 6 after being placed for 30 days

[0135] Specific embodiments Appearance Example 1 Weak moisture absorption without cracking Example 2 Weak moisture absorption without cracking Example 3 Weak moisture absorption without cracking Comparative Example 1 Collapse, unable to be cold pressed Comparative Example 2 Moisture absorption cracking Comparative Example 3 Moisture absorption cracking Comparative Example 4 Moisture absorption cracking Comparative Example 5 Moisture absorption cracking Comparative Example 6 Moisture absorption cracking

[0136] Table 1 shows the appearance of the miscible interstitial alloys prepared in Examples 1 to 3 and Comparative Examples 1 to 6 after being placed for 30 days. As can be seen from Table 1, Comparative Example 1 cannot be cold-pressed to form a miscible interstitial alloy; the miscible interstitial alloys prepared in Comparative Examples 2 to 6 all have the phenomenon of moisture absorption and cracking after being placed for 30 days; while the miscible interstitial alloys prepared in Examples 1 to 3 did not crack after being placed for 30 days. This shows that the present invention reduces the influence of the sodium silicate in the first component being easily absorbed by moisture in the air by adding silica sol to the first component and utilizing the extremely weak moisture absorption property of silica sol after sintering, thereby avoiding the cracking phenomenon of the prepared miscible interstitial alloy.

[0137] Figure 1 This is the appearance of the miscible interstitial alloy prepared in Example 1 after being placed for 180 days. Figure 1 It can be seen that the miscible interstitial alloy prepared in Example 1 has no obvious moisture absorption cracking phenomenon after being placed for 180 days, and there is no leakage of the second component and surface cracking phenomenon after multiple sintering. Figure 2 The appearance of the miscible interstitial alloy prepared in comparative example 7; (a) is the appearance of moisture absorption cracking after drying, (b) is the cross-sectional morphology, (c) is the appearance of the second component melting out after sintering, and (d) is the appearance of the second component melting out after sintering. Figure 2 It can be seen that the miscible interstitial alloy prepared by Comparative Example 7 exhibits obvious moisture absorption cracking, and the second component melts out after sintering. Compared with Comparative Example 7, that is, the miscible interstitial alloy prepared by the prior art, the miscible interstitial alloy prepared by the present invention has no obvious moisture absorption cracking phenomenon after being placed for 180 days, and no second component melts out after sintering.

[0138] 2. Mechanical properties test

[0139] The present invention conducts compression tests on the miscible interstitial alloys prepared in Examples 1 to 3 and Comparative Examples 1 to 6. The compression test refers to the GB / T 1964-2023 standard and is measured using a 50KN-class universal mechanical testing machine. The diameter of the miscible interstitial alloy is 30 mm, the height is 50 mm, and the compression rate is 1.0 mm / min. The results are shown in Table 2.

[0140] Table 2 Compressive strength of miscible interstitial alloys in Examples 1 to 3 and Comparative Examples 1 to 6

[0141]

[0142]

[0143] It can be seen from Table 1 that except for the miscible interstitial alloy prepared in Comparative Example 1 which collapsed and could not be cold-formed, the miscible interstitial alloys prepared in Examples 1 to 3 and Comparative Examples 2 to 6 all had certain compressive strength.

[0144] 3. Thermal conductivity test

[0145] The present invention adopts the international standard ISO 22007-2 to perform thermal conductivity tests on the miscible interstitial alloys prepared in Example 1 and Comparative Example 7, and conducts parallel experimental tests 5 times to obtain the corresponding thermal conductivity test range, wherein the diameter of the miscible interstitial alloy is 30 mm and the thickness is 20 mm to 25 mm.

[0146] The thermal conductivity of the miscible interstitial alloy in Comparative Example 7 is 56 W / mK, and the thermal conductivity of the miscible interstitial alloy prepared in Example 1 is 61.7 W / mK to 69.3 W / mK. Compared with the miscible interstitial alloy in Comparative Example 7, the thermal conductivity of the miscible interstitial alloy prepared by the present invention is improved by 10.7% to 24.2%.

[0147] 4. Hardness test

[0148] The present invention uses a Vickers microhardness tester to measure the microhardness of the miscible interstitial alloys prepared in Example 1 and Comparative Example 7. The loading force is 0.2kgf to 0.5kgf. The pressure is maintained for 15s after loading. Five points are measured and the average value is taken.

[0149] The surface hardness values ​​of the miscible interstitial alloys prepared in Example 1 and Comparative Example 7 are 4.52 HV and 2.47 HV, respectively. Compared with Comparative Example 7, the surface structural strength of the miscible interstitial alloy prepared in the present invention is greatly improved.

[0150] 5. Production cycle analysis

[0151] The present invention calculates the production cycle of the billet in the process of preparing the miscible interstitial alloy for Example 1 and Comparative Example 7 respectively. The production cycle of the billet in Comparative Example 7 is 2350 minutes; the production cycle of the billet in Example 1 is 330 minutes. Compared with Comparative Example 7, the production cycle of the billet in Example 1 is shortened by 86%. The subsequent pressing process and sintering process are the same. It shows that the production cycle used in the process of preparing the billet using the preparation method of the present invention is very short. At the same time, it avoids the complicated process of preparing the first component in the prior art, and solves the problem of complicated and time-consuming preparation process of the miscible interstitial alloy.

[0152] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a miscible interstitial alloy, characterized in that: The following steps are involved: Graphite and sodium silicate are used as a mixed matrix, and silica sol is introduced to form a first component; Using metal powder as the second component; The first component is used as a skeleton and the second component is used as a carrier, and the mixture is mixed to obtain a blank; Pressing the blank at room temperature to form a first alloy blank; Mixing silica sol, graphite powder and water to form a slurry, i.e., the third component; The third component is used as a protective layer and sprayed on the surface of the first alloy billet to form a second alloy billet; The second alloy billet is pressed at room temperature to form a final billet, and the final billet is sintered to obtain a miscible interstitial alloy.

2. The method for preparing a miscible interstitial alloy according to claim 1, characterized in that: The mass fraction of sodium silicate in the first component is 2wt% to 6wt%.

3. The method for preparing a miscible interstitial alloy according to claim 1, characterized in that: The mass fraction of the silica sol in the first component is 0.5wt% to 2.5wt%.

4. The method for preparing a miscible interstitial alloy according to claim 1, characterized in that: The mass fraction of graphite powder in the first component is 48wt% to 51wt%.

5. The method for preparing a miscible interstitial alloy according to claim 1, characterized in that: The spraying thickness of the third component is 0.7 mm to 1 mm.

6. The method for preparing a miscible interstitial alloy according to claim 1, characterized in that: The mass fraction of the silica sol in the third component is 15wt% to 20wt%, and the viscosity of the third component is controlled to be 30mPa·s to 38mPa·s.

7. The method for preparing a miscible interstitial alloy according to claim 1, characterized in that: The metal powder is one of Al, Cu, Zn, Sn and Al-Si alloy powder, and the particle size of the metal powder is 100 μm to 500 μm.

8. A miscible interstitial alloy prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the miscible interstitial alloy according to claim 8 in peak-shifting energy storage and thermal energy transfer.

Citation Information

Patent Citations

  • Alloys with inverse microstructures

    WO2014063191A1

Cited By

  • Miscibility gap alloy, and preparation method therefor and use thereof

    WO2025185778A1